2014
DOI: 10.1111/bjd.12813
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous frameshift mutation in keratin 5 in a family with G alli– G alli disease

Abstract: BackgroundReticulate pigmentary disorders include the rare autosomal dominant Galli–Galli disease (GGD) and Dowling–Degos disease (DDD). Clinical diagnosis between some of the subtypes can be difficult due to a degree of overlap between clinical features, therefore analysis at the molecular level may be necessary to confirm the diagnosis.ObjectivesTo identify the underlying genetic defect in a 48-year-old Asian-American woman with a clinical diagnosis of GGD.MethodsHistological analysis was performed on a skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…In light of substantial clinical, histological and mutational overlap between GGD and DDD, they are considered to belong to the same entity 2, 3. Mutations in KRT5 (encoding keratin 5) have been associated with GGD/DDD since 2006 2, 3, 4, 5. With the development of whole‐exome sequencing, mutations in POFUT1 (encoding protein O ‐fucosyltransferase 1)6, 7 and POGLUT1 (encoding protein O ‐glucosyltransferase 1)8 have been shown to underlie some cases of GGD/DDD.…”
mentioning
confidence: 99%
“…In light of substantial clinical, histological and mutational overlap between GGD and DDD, they are considered to belong to the same entity 2, 3. Mutations in KRT5 (encoding keratin 5) have been associated with GGD/DDD since 2006 2, 3, 4, 5. With the development of whole‐exome sequencing, mutations in POFUT1 (encoding protein O ‐fucosyltransferase 1)6, 7 and POGLUT1 (encoding protein O ‐glucosyltransferase 1)8 have been shown to underlie some cases of GGD/DDD.…”
mentioning
confidence: 99%
“…Most cases were reported from Germany, in which c.418dupA was described as the most common mutation in patients with acantholytic DDD. Further mutations were described in Spanish, Arabic, Asian‐American, Chinese and Indian patients . In some cases, acantholysis was not observed, and it has also been reported that acantholysis may not necessarily be present at all times or at all anatomical sites .…”
mentioning
confidence: 99%
“…Further mutations were described in Spanish, Arabic, Asian‐American, Chinese and Indian patients . In some cases, acantholysis was not observed, and it has also been reported that acantholysis may not necessarily be present at all times or at all anatomical sites . In many cases, both from Europe and Asia, an association between DDD/GGD and a KRT5 mutation could not be detected.…”
mentioning
confidence: 99%
See 2 more Smart Citations